Optical properties of CDOM and assessing eutrophication by remote sensing of CDOM in the Zhanjiang Bay, China - Zhong, Yafeng; Yu, Guo; Fu, Dongyang; Chen, Fajin; Luo, Yafei; Deng, Ruozhao (Frontiers in Marine Science, 2025)
Based on the field survey data collected in winter (January, 2018) and spring (April, 2017), the characteristic variability of chromophoric dissolved organic matter (CDOM) in different seasons in Zhanjiang Bay was analyzed. The results demonstrated that CDOM absorption coefficient at 280 nm (ag(280)) and the spectral slope from 275 to 295 nm (S275-295) representing the molecular weight of CDOM could both maintain good correlations with salinity in winter and spring, indicating that CDOM was more likely to exist as a conserved substance during its migration in Zhanjiang Bay. The characteristics of CDOM and the weak correlation between Chlorophyll a (Chl a) and CDOM revealed that the influence of algal activity on CDOM was limited. In addition, this study also suggested the idea of using CDOM to track the eutrophication of a bay. Based on the acceptable correlation between ag(280) and reflectance band ratio (Rrs(704)/Rrs(492)) recorded in-situ, and eutrophication index (EI), a series of empirical models were developed to categorize and retrieve the eutrophication through ag(280) and were then used to Sentinel-2. The eutrophication assessment of Zhanjiang Bay was examined by CDOM remote sensing. This study provided a fresh approach to measuring eutrophication that could help regional environmental quality management organizations to make informed decisions.